2017
DOI: 10.1128/mcb.00630-16
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism To Switch the Aryl Hydrocarbon Receptor from a Transcription Factor to an E3 Ubiquitin Ligase

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is known as a mediator of toxic responses. Recently, it was shown that the AhR has dual functions. Besides being a transcription factor, it also possesses an intrinsic E3 ubiquitin ligase function that targets, e.g., the steroid receptors for proteasomal degradation. The aim of this study was to identify the molecular switch that determines whether the AhR acts as a transcription factor or an E3 ubiquitin ligase. To do this, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…The progression from inflammation to tumorigenesis is well established ( Schäfer and Werner, 2008 ) and our mice readily developed mixed colon adenomas/adenocarcinomas in the standard AOM/DSS model in line with previous data in global Ahr −/− mice ( Díaz-Díaz et al., 2016 ) or even with the mutagen AOM alone. In vitro studies on cell lines proposed that AHR functions as part of an E3 ubiquitin ligase complex that serves to ubiquinate β-catenin and target it for degradation ( Luecke-Johansson et al., 2017 , Ohtake et al., 2007 ). Our results provide evidence that Wnt-β-catenin pathway dysregulation in Ahr -deficient IECs occurred upstream of β-catenin degradation, affecting the response to WNT signals themselves through the expression of the two related E3 ubiquitin ligases (ZNRF3 and RNF43) that degrade the Wnt frizzled receptors ( Koo et al., 2012 ) in LGR5 + stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The progression from inflammation to tumorigenesis is well established ( Schäfer and Werner, 2008 ) and our mice readily developed mixed colon adenomas/adenocarcinomas in the standard AOM/DSS model in line with previous data in global Ahr −/− mice ( Díaz-Díaz et al., 2016 ) or even with the mutagen AOM alone. In vitro studies on cell lines proposed that AHR functions as part of an E3 ubiquitin ligase complex that serves to ubiquinate β-catenin and target it for degradation ( Luecke-Johansson et al., 2017 , Ohtake et al., 2007 ). Our results provide evidence that Wnt-β-catenin pathway dysregulation in Ahr -deficient IECs occurred upstream of β-catenin degradation, affecting the response to WNT signals themselves through the expression of the two related E3 ubiquitin ligases (ZNRF3 and RNF43) that degrade the Wnt frizzled receptors ( Koo et al., 2012 ) in LGR5 + stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Compared with IgG antibody control, AhR recruitment peaked at 1 h posttreatment, suggesting that BSO can trigger AhR transcriptional activity as rapidly as the well-characterized AhR ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin (18,19). Immunocytochemistry assay showed a high frequency of cells positive for nuclear AhR after 2 h of exposure to BSO compared with control conditions ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…A recent detailed study on the interaction between AhR and CUL4B using human cell lines presented conflicting data compared to work by Ohtake and colleagues [15]. Luecke-Johansson and colleagues could not identify Arnt as a part of the CUL4B/AhR complex when performing co-immunoprecipitations with a CUL4B antibody, even after treatment with TCDD, although Arnt had been shown to be essential for the binding between AhR and CUL4B in the previous report [35]. Moreover, a recent study showed that over-expression of CUL4B increased β-catenin accumulation.…”
Section: Discussionmentioning
confidence: 99%